Luther. Season 2 [videorecording (DVD)] - Elba, Idris; Wilson, Ruth, 1982-; Crowley, Dermot; Cross, Neil; Miller, Sam, 1962 September 28- (BBC Video : Burbank, CA : Distributed by Warner Home Video, 2011)
Collects the second season of the television program "Luther" in which Luther, a brilliant and tormented police detective, investigates serial murder cases.